DIGITAL MARKETING STRATEGIES FOR KUCEKIN LAUNDRY MSMEs - Ardiansyah Rasyid; Erwin Wangsadjaja; Jevon Andina Dragon; Wellson Arta (Transpublika Publisher, 2024)
Digital marketing strategies involve activities that responsibly address social and environmental aspects while meeting the needs of consumers and businesses. The training target is a laundry business located in West Jakarta, which faces numerous challenges, particularly in digital marketing. The goal of this activity is to help the business enhance its digital marketing knowledge to boost sales. The training method involves face-to-face sessions focusing on digital marketing, including how the business interacts with its environment and stakeholders. This strategy aims to improve brand loyalty, enhance employee and customer satisfaction, ensure compliance with regulations, and increase profitability. Through this activity, it is hoped that the issues faced by the business can be resolved, thereby improving its sustainability and effectiveness in marketing its services. The outcomes of this activity will include publications in journals and intellectual property rights (HAKI).